2017
DOI: 10.3153/jfhs17020
|View full text |Cite
|
Sign up to set email alerts
|

BLACK CUMIN (Nigella sativa) AND ITS ACTIVE COMPONENT OF THYMOQUINONE: EFFECTS ON HEALTH

Abstract: Abstract:Nigella sativa has the richest historical past of plants in the healthcare field. It has been used as a food preservative and to enhance flavour in many countries of the world for thousands of years and has also been used as a spice, and Nigella sativa seed and oil has been consumed for the treatment of many diseases in the world for many years. Today, it is believed to have antihypertensive, antihyperlipidemic, antidiabetic, anticancer, antioxidant, antimicrobial, antitumour, antibacterial, anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…The results presented here demonstrate greater than that or the previous studies [ 49 ], which found that ethyl alcohol extract of N. sativa exhibited antibacterial potency against B. subtilis with an inhibition diameter of 7 mm. The results of the study presented here are also more potent than that reported previously [ 32 ], which indicated that the antibacterial potency of EO-NS was greater on S. aureus (MTCC 9542) with an inhibition diameter of 16 mm than Vibrio harveyi (MTCC 7771) with an inhibition diameter of 5 mm for the 10 mg/mL concentration. EO-NS exhibits potent antibacterial activities against antibiotic-resistant bacterial strains (gram-negative and gram-positive), thereby advocating the utility of the bioactive molecules contained in EO-NS as an alternative to commercially available antibiotics to combat bacterial resistance.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The results presented here demonstrate greater than that or the previous studies [ 49 ], which found that ethyl alcohol extract of N. sativa exhibited antibacterial potency against B. subtilis with an inhibition diameter of 7 mm. The results of the study presented here are also more potent than that reported previously [ 32 ], which indicated that the antibacterial potency of EO-NS was greater on S. aureus (MTCC 9542) with an inhibition diameter of 16 mm than Vibrio harveyi (MTCC 7771) with an inhibition diameter of 5 mm for the 10 mg/mL concentration. EO-NS exhibits potent antibacterial activities against antibiotic-resistant bacterial strains (gram-negative and gram-positive), thereby advocating the utility of the bioactive molecules contained in EO-NS as an alternative to commercially available antibiotics to combat bacterial resistance.…”
Section: Resultssupporting
confidence: 58%
“…Various components in EOs, including terpenes, sesquiterpenes, and phenolic compounds, which function in diverse modes, can be linked to their antioxidant properties. The principal phytoconstituents EO-NS were O -cymene, carvacrol, 4-terpineol, and longifolene, which were responsible for antioxidant properties of EO-NS [ 15 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Indian alternative system of treatments (Ayurveda and Siddha) effectively uses it for immune-boosting activity due to the presence of THQ and nigellone (Abdallah, 2017). The effectiveness in common cold is also reported (Ermumcu & Şanlıer, 2017). NS raises the level of CD8 cell and enhances the immunity in bronchial asthma and allergic rhinitis.…”
Section: Discussionmentioning
confidence: 91%
“…THQ is less toxic in vivo and in vitro at a dose of 20-500 mg/kg; however, it was found toxic in a dose of 500 mg/kg on the histopathological level in the form of oil in rats (Ermumcu & Şanlıer, 2017). In vitro, the toxicity of THQ was tested in rat hepatocyte cultures both for cyto and genotoxicity and found that THQ produces genotoxic and cytotoxic effects at concentrations ≥ 25 mM (Khader et al, 2009).…”
Section: Toxicity Studiesmentioning
confidence: 99%
“…The significance of nigella has a long history in human culture, as it was used as a spice, traditional herbs, and food preservative, as well as enhancing the flavor of bakeries (Karaçil Ermumucu and Şanlıer, 2017). Black cumin seed is a good alternative crop for small landholders because of its local consumption and other benefits, such as oil and oleoresin for medical purposes, export market, crop diversification, revenue generation, and others (Anshiso and Teshome, 2018).…”
Section: Importance Of Nigellamentioning
confidence: 99%